A population‐based study of head injury, cognitive function and pathological markers. Issue 4 (11th March 2021) - James, Sarah‐Naomi; Nicholas, Jennifer M.; Lane, Christopher A.; Parker, Thomas D.; Lu, Kirsty; Keshavan, Ashvini; Buchanan, Sarah M.; Keuss, Sarah E.; Murray‐Smith, Heidi; Wong, Andrew; Cash, David M.; Malone, Ian B.; et al.
Abstract: Objective: To assess associations between head injury (HI) with loss of consciousness (LOC), ageing and markers of later‐life cerebral pathology; and to explore whether those effects may help explain subtle cognitive deficits in dementia‐free individuals. Methods: Participants ( n = 502, age = 69–71) from the 1946 British Birth Cohort underwent cognitive testing (subtests of Preclinical Alzheimer Cognitive Composite), 18 F‐florbetapir A β ‐PET and MR imaging. Measures include A β ‐PET status, brain, hippocampal and white matter hyperintensity (WMH) volumes, normal appearing white matter (NAWM) microstructure, Alzheimer's disease (AD)‐related cortical thickness, and serum neurofilament light chain (NFL). LOC HI metrics include HI occurring: (i) >15 years prior to the scan (ii) anytime up to age 71. Results: Compared to those with no evidence of an LOC HI, only those reporting an LOC HI>15 years prior (16%, n = 80) performed worse on cognitive tests at age 69–71, taking into account premorbid cognition, particularly on the digit‐symbol substitution test (DSST). Smaller brain volume (BV) and adverse NAWM microstructural integrity explained 30% and 16% of the relationship between HI and DSST, respectively. We found no evidence that LOC HI was associated with A β load, hippocampal volume, WMH volume, AD‐related cortical thickness or NFL (all p > 0.01). Interpretation: Having a LOC HI aged 50's and younger was linked with lower later‐life cognitive function at age 70 than expected. This may reflect a damaging but small impact of HI; explained in part by smaller BV and different microstructure pathways but not via pathology related to AD (amyloid, hippocampal volume, AD cortical thickness) or ongoing neurodegeneration (serum NFL).